Greed in Hamka's Novel Merantau ke Deli - Pardi pardi (International Journal of English and Applied Linguistics (IJEAL), 2021)
Merantau ke Deli is a novel written by Hamka published in 1939. The main theme of this novel is about Minangkabaunese culture and the conflict in the marriage of Leman, a Minangkabaunese, and Poniem, a Javanese. Adat law makes Leman married Mariatun, a Minangkabaunese as his second wife. The focus of this study is on the act of Greed performed by Leman and Mariatun. This is descriptive qualitative research based on Miles, Huberman, and Saldana (2014). The theory of Greed stated by Kets De Vries (2016) was used to analyze the data obtained. The results show two kinds of Greed in the novel; the Greed for the woman's beauty and the Greed for poverty. Leman performs the Greed on the woman's beauty to marry Poniem, although it is forbidden for Minangkabaunese man to marry a non-Minangkabaunese woman. Poniem's beauty makes him break the adat law. The greediness of a beautiful woman also happens when he meets Mariatun, a beautiful young woman from the Minangkabaunese tribe. The greediness on poverty showed by Mariatun for taking the batik and also for dominating Leman's poverty. However, the acts of Greed performed by the characters in the novel create tragic flaws in their future life.